Digital content management. First educational application of CONTENTdm at the university: Bachelor and Master Studies in the Faculty of Information Science of the UCM - López Hurtado, Mariana; Valentín Ruiz, Francisco José; Olivera Zaldua, María (Revista General de Información y Documentación, 2012)
More and more documents are created in digital format, so it is essential the proper management and dissemination of them. The services in the cloud are among the systems for the processing of such digital content that have been better received in recent times. The first teaching experience in Spanish's university with the management software of OCLC, CONTENTdm, applied to the audiovisual collection of the Faculty of Information Science of the UCM is presented as a model in this article.
Keywords: CONTENTdm; Digital content management; Digital collections; Cloud computing; Educational applications; OCLC; Universidad Complutense de Madrid.